Long-term lifestyle changes after colorectal cancer screening: randomised controlled trial. Issue 8 (2nd September 2014) - Berstad, Paula; Løberg, Magnus; Larsen, Inger Kristin; Kalager, Mette; Holme, Øyvind; Botteri, Edoardo; Bretthauer, Michael; Hoff, Geir
Abstract : Objective: There is uncertainty whether cancer screening affects participant incentives for favourable lifestyle. The present study investigates long-term effects of colorectal cancer (CRC) screening on lifestyle changes. Design: In 1999–2001, men and women drawn from the population registry were randomised to screening for CRC by flexible sigmoidoscopy ('invited-to-screening' arm) or to no-screening (control arm) in the Norwegian Colorectal Cancer Prevention trial. A subgroup of 3043 individuals in the 'invited-to-screening' and 2819 in the control arm, aged 50–55 years, randomised during 2001 had their lifestyle assessed by a questionnaire at inclusion and after 11 years (42% of cohort). The outcome was 11-year changes in lifestyle factors (body weight, smoking status, physical exercise, selected dietary habits) and in total lifestyle score (0–4 points, translating to the number of lifestyle recommendations adhered to). We compared outcomes in the two randomisation arms and attendees with positive versus negative findings. Results: Total lifestyle scores improved in both arms. The improvement was smaller in the 'invited-to-screening' arm (score 1.43 at inclusion; 1.58 after 11 years) compared with the control arm (score 1.49 at inclusion; 1.67 after 11 years); adjusted difference −0.05 (95% CI −0.09 to −0.01; p=0.03). The change in the score was less favourable in screening attendees with a positive compared with negative screening result; adjusted difference −0.16 (95% CI −0.25 to −0.08; p<0.001). Conclusions: The present study suggests that possible unfavourable lifestyle changes after CRC screening are modest. Lifestyle counselling may be considered as part of cancer screening programmes. Trial registration number: NCT00119912.